Metabolism of sulfamethoxazole in Arabidopsis thaliana cells and cucumber seedlings. (November 2018) - Dudley, Stacia; Sun, Chengliang; Jiang, Ji; Gan, Jay
Abstract: Reclaimed water is a historically underutilized resource. However, with increased population growth and global climate change, reclaimed water is evolving into an economical and sustainable water resource to meet the needs of citizens, industries, and agriculture. The use of recycled water for agricultural irrigation comes with the potential risk of environmental and food contamination by pharmaceuticals and personal care products (PPCPs). The levels of PPCPs in plants will depend on translocation and metabolism in plant tissues. However, relatively little is known about the metabolism of PPCPs in plants. In this study, the metabolism of the antibiotic sulfamethoxazole was investigated in Arabidopsis thaliana cells as well as cucumber seedlings grown under hydroponic conditions. Using high-resolution mass spectrometry and 14 C tracing allowed for sulfamethoxazole metabolism to be comprehensively characterized through all metabolic phases. Six phase I and II metabolites were identified in A. thaliana cell cultures and cucumber seedlings. Sulfamethoxazole metabolism followed oxidation and then rapid conjugation with glutathione and leucine. Direct conjugation with the parent compound was also observed via acetylation and glucosylation. At the end of 96 and 168 h incubation, N4-acetylsulfamethoxazole was the major metabolite and >50% of the radiolabeled sulfamethoxazole became non-extractable in both A. thaliana cells and cucumber seedlings suggesting extensive phase III metabolism and detoxification. The study findings provided information for a better understanding of the uptake and metabolism of sulfamethoxazole in higher plants, highlighting the need to consider metabolic intermediates and terminal fate when assessing the risk of PPCPs in the soil-plant continuum. Graphical abstract: Image 1